Navigating the aftermath: Risk factors of recurrence following coronary bypass surgery in Indonesia - Bachtiar, Adang; Candi, Cicilya; Hasibuan, Syarif R.; Widyasanti, Nisrina; Kusuma, Dian (Narra J, 2024)
Coronary heart disease (CHD) remains a leading cause of mortality in Indonesia, and coronary artery bypass graft (CABG) surgery is frequently employed to manage arterial blockages. Despite its efficacy, the recurrence of heart disease post-surgery is a significant concern, highlighting the need for a deeper understanding of its influencing factors. The aim of this study was to examine the factors associated with the incidence of heart disease recurrence after coronary bypass surgery. This study employed a prospective observational design, analyzing hospital claim data from Indonesia's Social Security Agency for Health, known as Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan, from 2017 to 2022. The analysis included 5,947 patients who survived CABG surgery. Multivariable logistic regression was utilized to assess the relationship between patient demographics, comorbidities, socioeconomic status, and compliance with follow-up visits, as well as their impact on the recurrence of cardiovascular disease. The study found that 24.1% of patients experienced hospitalization recurrence. Patients with irregular follow-ups were less likely to experience recurrence (adjusted odds ratio (AOR): 0.63; 95%CI: 0.51–0.78). Other significant risk factors for recurrence included being self-employed (AOR: 2.09; 95%CI: 1.72–2.55), having comorbid conditions such as disorders of fluid, electrolyte, and acid-base balance (AOR: 3.55; 95%CI: 2.97–4.24), and experiencing cerebral infarction or stroke (AOR: 10.85; 95%CI: 8.24–14.29). In contrast, older age (AOR: 0.89; 95%CI: 0.88–0.91) and the presence of non-insulin-dependent diabetes mellitus (AOR: 0.35; 95%CI: 0.29–0.42) were associated with a lower risk of recurrence. Sex did not significantly influence the risk of recurrence (AOR: 1.18; 95%CI: 0.86–1.62). In conclusion, the study indicates a considerable rate of cardiovascular disease recurrence post-CABG in Indonesia, highlighting several key risk factors. Tailored postoperative management and strict adherence to follow-up protocols are essential for mitigating recurrence. These findings offer crucial insights for improving post-CABG health management strategies in Indonesia.